Millet survival submitted to associated stress using generalized gamma and Burr XII distribution (Research, Society and Development, 2020)
Water and saline stresses are the main factors affecting agricultural production. Millet is tolerant to these abiotic stresses and cultivated in regions with scarcity of rain and used for the production of grains and pastures. The knowledge of the lifetime of forage plants provides very useful information on cultivation and management of populations. The objective was to evaluate the lifetime of millet under conditions of water and saline stress using survival analysis. The experiment was carried in 48 millet plants submitted the water and saline deficit, for 4 cycles of 105 days. To estimate the lifetime of the millet, we used the survival functions of the probability distributions: exponential, Weibull, Gumbel, log-normal, Gompertz, logistics, Gamma, generalized Gamma, Burr XII and Birnbaum-Saunders and the Kaplan-Meier estimator. The lifetime of 64.6% of the plants was less than 105 days. Using the Kaplan-Meier estimator, 50% of plants survive up to 65th day, using the generalized Gamma and Burr XII survival function this rate occurs on the 75th day. The generalized Gamma and Burr XII survival function are alternatives to estimate the lifetime of millet submitted to conditions of water and saline stress.